A new brachypterous genus of Brazilian stag beetle (Coleoptera: Lucanidae: Lucaninae) with description of three new species - Grossi, Paschoal Coelho (Zootaxa, 2016)
Montesinus gen. nov. is described from Brazil, along with three new species, Montesinus monnei sp. nov. (Holotype male deposited in MNRJ: Brazil, Espírito Santo State, Parque Nacional do Caparaó, 2500 m a.s.l., 13.IV.2001, F.O. Correia leg.), M. tatula sp. nov. (Holotype female deposited in CERPE: Brazil, Minas Gerais State, Corinto, 900 m a.s.l., I.1998, E. Antunes leg.), and M. machadoi sp. nov. (Holotype female deposited in MNRJ: Brazil, Espírito Santo State, Serra do Caparaó, Ibitirama, 2600 m a.s.l., 10–12.IV.2012, M.V.P. Simões leg.). This unusual genus is related to Altitatiayus Weinreich, with which it shares the brachypterous condition and also some characters of the male genitalia, being distinguished from it mainly by its punctate flat head and indistinct elytral striae. The three new species are distinguished by their general color, shape of posterior margin of pronotum, tibial armature and elytral punctures. The new species are from two isolated mountain formations, called Serra do Caparaó and Serra do Espinhaço formations. This is the third brachypterous genus of stag beetle found in Brazil, but it occurs in mountains isolated from the Serra da Mantiqueira where the other two genera are found. The habitus, male genitalia and maxillae of the new species are illustrated.